Educational robotics - Huang, Xianyun (2017)
Automation is said to next upcoming technological revolution. With just a few clicks away from office, automated system such as robots and optical tweezers can perform tasks for us effectively and conveniently. Nevertheless, it is essential to understand the functionality and implemented software in order to control these automated systems. In this project, a Java Graphical User Interface (GUI) is devised to educate students about robotics and automation. Robotics involves programming that bring Science, Engineering and Mathematics together. Through this Java program, students can grasp the concepts of these subjects and learn programming. A server-client model is developed to connect and control the microscope system remotely. The built-in controller system coded in LabVIEW is able to detect the position of the motorized stage in real-time and records the positions of trajectory points in a notepad text file. The file can be retrieved from the controller and a trajectory path is plotted in the GUI. The data can also be used to calculate the error of the control system. Students can view the trajectory path of the movement of microscope motorized stage and together with an error plot. This can reinforce the knowledge on control system and make learning more interesting.